Severe haemoptysis in a 5 year old child with Kartagener’s syndrome: case report - S., Mohinish; K., Mallesh; K., Prashanth H.; R., Ravichandra K. (International Journal of Contemporary Pediatrics, 2020)
Kartagener`s syndrome, a rare autosomal recessive disorder is a type of Primary Ciliary Dyskinesia (PCD) associated situs inversus, bronchiectasis, sinusitis and male infertility. We present a case of a 5-year-old girl who came with features of bilateral glue ear, recurrent sinusitis, recurrent hemoptysis and dextrocardia. She was diagnosed to have Kartagener`s syndrome and was evaluated for recurrent hemoptysis.